LAND OF THE LOST. (From Abba to Zoom: A Pop Culture Encyclopedia of the Late 20th Century, 2005)
Information on the science-fiction television series "Land of the Lost," is presented. The program was aired on Saturday mornings from 1974 to 1978. It was produced by Sid Krofft and Marty Krofft. The program starred actors including Spencer Milligan, Wesley Eure, and Kathy Coleman.